2016
DOI: 10.1242/dev.142075
|View full text |Cite
|
Sign up to set email alerts
|

Cycling through developmental decisions: how cell cycle dynamics control pluripotency, differentiation and reprogramming

Abstract: A strong connection exists between the cell cycle and mechanisms required for executing cell fate decisions in a wide-range of developmental contexts. Terminal differentiation is often associated with cell cycle exit, whereas cell fate switches are frequently linked to cell cycle transitions in dividing cells. These phenomena have been investigated in the context of reprogramming, differentiation and trans-differentiation but the underpinning molecular mechanisms remain unclear. Most progress to address the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
136
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 141 publications
12
136
0
1
Order By: Relevance
“…In fact, the rapid decrease in Plk2 mRNA expression on LN‐CPC contact preceded, and was causatively linked to, the reduced CPC proliferation, which was absent when Plk2 mRNA expression was preserved, such as in CPCs on FN or in Flag‐Plk2–transfected CPCs on LN. Slowing of cell proliferation is associated with prolongation of the gap phases, the most critical phases for lineage programming and initiation of differentiation . Considering the spontaneous differentiation that can be observed in pluripotent stem cells when the G 1 phase is prolonged and the prolongation of the G 1 phase because of delayed entry into the S phase that occurs in Plk2 ‐/‐ embryonic fibroblasts, decreased expression of Plk2 may mark the timing of early lineage programming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the rapid decrease in Plk2 mRNA expression on LN‐CPC contact preceded, and was causatively linked to, the reduced CPC proliferation, which was absent when Plk2 mRNA expression was preserved, such as in CPCs on FN or in Flag‐Plk2–transfected CPCs on LN. Slowing of cell proliferation is associated with prolongation of the gap phases, the most critical phases for lineage programming and initiation of differentiation . Considering the spontaneous differentiation that can be observed in pluripotent stem cells when the G 1 phase is prolonged and the prolongation of the G 1 phase because of delayed entry into the S phase that occurs in Plk2 ‐/‐ embryonic fibroblasts, decreased expression of Plk2 may mark the timing of early lineage programming.…”
Section: Discussionmentioning
confidence: 99%
“…Slowing of cell proliferation is associated with prolongation of the gap phases, the most critical phases for lineage programming and initiation of differentiation. 53 Considering the spontaneous differentiation that can be observed in pluripotent stem cells when the G 1 phase is prolonged 54,55 and the prolongation of the G 1 phase because of delayed entry into the S phase that occurs in Plk2 -/embryonic fibroblasts, 56 decreased expression of Plk2 may mark the timing of early lineage programming. Consistent with this hypothesis, we found that Plk2 expression inversely regulated the expression of cardiac lineage genes.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Aurora-B triggers the release of chromatin-bound RNAs and core transcription factors suggests that Aurora-B may be a key factor responsible for resetting the transcriptional program as cells pass through mitosis. Passage through mitosis is a key step mediating transcriptional reprogramming and cell fate transitions (Egli, Birkhoff, & Eggan, 2008;Soufi & Dalton, 2016), and our work suggests that phosphorylation of SAF-A may be a key component of this process.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, cell cycle arrest at the G1/S checkpoint by a variety of mechanism including serum withdrawal significantly enhances the transdifferentiation of fibroblasts to neurons [9]. As mitotic cells integrate extracellular and intracellular information during G1 to determine whether it is suitable to commit to the replication of genomic DNA, cells synchronized at G1 offers the optimal timing for conversion into post-mitotic cells such as neurons [81], [82].…”
Section: Mechanism Of Transdifferentiationmentioning
confidence: 99%